The Role of the East Kalimantan Provincial Government in the Sustainability of the CSR Program of Coal Mining Companies for the Community Around Mining - Putra, Faiq Muhammad Norestia; Sari, Resma Yuvita; Noor, Muhammad (HK-Publishing, 2024)
AbstractCorporate Social Responsibility (CSR) is a concept or action undertaken in the business or industrial world as a form of responsibility for surrounding communities' social and environmental well-being. The East Kalimantan Provincial Government plays a critical role in ensuring the sustainability of CSR programs by coal mining companies to enhance the quality of life for communities around mining areas. Through strategic policies, the provincial government integrates corporate CSR programs with regional development agendas to ensure that contributions from the mining industry sector have optimal and sustainable impacts. In fulfilling its role, the local government collaborates with various stakeholders to supervise, evaluate, and improve the implementation of CSR programs. The main focus is on improving infrastructure, education, health, and local economic empowerment. Additionally, the provincial government also acts as a mediator between the companies and the community, ensuring that the aspirations and needs of the community are accommodated in each program implemented. Thus, the role of the East Kalimantan Provincial Government is crucial in creating synergy between industrial growth and the welfare of local communities, facilitating an inclusive and sustainable socio-economic transformation in the coal mining region.Keywords: Corporate Social Responsibility (CSR), East Kalimantan Provincial Government, Supervision and Evaluation.